2019
DOI: 10.3847/2041-8213/ab4799
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Jet in a Polar Limb of the Solar Coronal Hole

Abstract: A new type of chromospheric jet in a polar limb of a coronal hole is discovered in the Ca ii filtergram of the Solar Optical Telescope on board the Hinode. We identify 30 jets in a filtered Ca ii movie with a duration of 53 minutes. The average speed at their maximum heights is found to be 132 ± 44 km s−1 ranging from 57 to 264 km s−1 along the propagation direction. The average lifetime is 20 ± 6 ranging from 11 to 36 s. The speed and lifetime of the jets are located at end-tails of those parameters determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Recently Cho et al (2019) reported on a new type of faint chromospheric jets detected at a limb in Ca II Hinode images. These jets exhibit an average speed of about 132 km s −1 and an average lifetime of 20 s, ranging from 11 to 36 s. These new limb jets could be related to the short lived RBEs discussed here.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently Cho et al (2019) reported on a new type of faint chromospheric jets detected at a limb in Ca II Hinode images. These jets exhibit an average speed of about 132 km s −1 and an average lifetime of 20 s, ranging from 11 to 36 s. These new limb jets could be related to the short lived RBEs discussed here.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Polar coronal holes have been intensively studied from the ecliptic plane (e.g. Chandrashekhar et al 2014;Gupta 2014;Spadaro et al 2017;Hahn et al 2018;Cho et al 2019;Tei et al 2020;Peleikis et al 2017;), but lack of imaging from outside the ecliptic has so far limited our understanding of the geometry of polar structures. As described in Section 2.2.2, the magnetic flux in the heliosphere varies with the solar cycle.…”
Section: What Are the Properties Of The Magnetic Field At High Solar ...mentioning
confidence: 99%